Connecting Women National and International Networks during the Long Nineteenth Century - Costa, Jaime (2021)
Women's networks proliferated during the long nineteenth century in the Atlantic World and began spreading globally. Connecting Women features presentations from the second conference of the Intercontinental Cross-Currents Network, "The Dynamics of Power: Inclusion and Exclusion in Women's Networks during the Long Nineteenth Century," held in 2016 at the University of Minho in Braga, Portugal. Intercontinental Cross-Currents provides a cooperative platform for researchers from all scholarly disciplines interested in the literal and metaphorical networks created and navigated by women from the European and American continents from 1776 to 1939-the so-called long nineteenth century. Organized by the University's Institute of Arts and Humanities' Centre for Humanistic Studies and the Department of English and North American Studies, the conference brought together international participants who investigated mechanisms of inclusion and exclusion within women's networks forged in Britain, France, Italy, the Philippines, Portugal, and the United States. Connecting Women delves into both literary networks and those with social and political agendas that centered around temperance associations, anti-slavery societies, crime syndicates, suffragism, political organizations, and war relief.